ChemInform Abstract: Zinc‐Catalyzed Dehydrogenative N‐Silylation of Indoles with Hydrosilanes. Issue 1 (3rd January 2013) - Tsuchimoto, Teruhisa; Iketani, Yoshihiko; Sekine, Masaru
Abstract Zinc triflate in a nitrile solvent is an effective catalyst for the title reaction of indoles with an substituent at any of the six possible positions, as well as pyrroles and carbazoles.